Exploring Organizational Innovativeness Factors Influencing Sustainable Construction Adoption - Bamgbade, Jibril Adewale; Kamaruddeen, A.M.; Mohd Nawi, Mohd Nasrun; Ali, ﻿Basharat (MAYFEB TECHNOLOGY DEVELOPMENT Toronto, Ontario, Canada, 2017)
The aim of this paper is to empirically explore the organizational innovativeness dimensio ns (product and process innovativeness) influencing large contractors’ adoption of sustainable construction.Mailed and personally administered questionnaire survey methods were used to collect data from a stratified sample of Malaysian large contracting firms.Using Partial Least Squares Structural Equation Modeling (PLS SEM) technique, a number of 172 responses were analyzed.An important contribution of this paper is that enhanced organizational innovativeness relates strongly to the adoption of sustainable construction practices. This suggests that the organizational innovativeness dimensions considered in this study are indeed robust to predict the adop tion of sustainable construction by the contractors.Although, this study focused on examining the factors influencing contractors’ adoption of a set of sustainability dimensions such as environmental, social and economic sustainability, it did not differentiate between these factors that are influencing each of these dimensions.The framework developed in this study can be used by the construction industry firms and other stakeholders not only to gain competitive advantage within the industry, but also to develop better strategies towards increasing the adoption of sustainable construction delivery in project execution.